Coral reef partners - Ethan, Eric.; Bearanger, Marie (Milwaukee, Wis. : Gareth Stevens Publishing, 1997)
This book describes some of the symbiotic relationships that help preserve the fragile coral reef ecosystem.
Includes index.
Includes glossary.
Includes bibliography.
4-8
Keywords: Coral reef ecology; Symbiosis; Ecology